Dry Matter Production and Partitioning, Yield, Quality and Nutrient Uptake of Sweet Potato (Ipomoea batatas L.) as Influenced by Irrigation and Fertilizer Levels - Biswal, S; Nedunchezhiyan, M; Mohapatra, PK (JOURNAL OF ROOT CROPS, 2017)
A field experiment was conducted for two rabi seasons at the Instructional Farm, Krishi Vigyan Kendra, Orissa University of Agriculture and Technology, Barachana, Odisha to study the effect of irrigation and fertilizer levels on dry matter production and partitioning, yield, quality and nutrient uptake of sweet potato (Ipomoea batatas L.). The experiment was conducted in split plot design with three replications. The irrigation levels were assigned to main plots (I1 = IW/CPE 0.6, I2 = IW/CPE 0.8, I3 = IW/CPE 1.0 and I4 = IW/CPE 1.2) and fertility levels to sub plots (F1 = N-P2O5-K2O @ 0-0-0 kg ha-1, F2 = N-P2O5-K2O @ 50-50-50 kg ha-1, F3 = N-P2O5-K2O @ 50-50-75 kg ha-1, F4 = N-P2O5-K2O @ 75-50-75 kg ha-1, F5 = N-P2O5-K2O @ 75-50-100 kg ha-1 and F6 = N-P2O5-K2O @ 75-50-125 kg ha-1). The results revealed that dry matter accumulation in leaves and stems was greater with irrigation at IW/CPE 1.2 and N-P2O5-K2O @ 75-50-125 kg ha-1. The dry matter accumulation in tuber was greater with irrigation at IW/CPE 0.8. The application of N-P2O5-K2O @ 75-50-75 kg ha-1 resulted in greater tuber yield. The maximum tuber yield and nutrient uptake (NPK) were obtained with the application of N-P2O5-K2O @75-50-75 kg ha-1 at IW/CPE 0.8. The starch and protein contents increased with increase in irrigation levels up to IW/CPE 1.0. The starch content in tuber increased up to N-P2O5-K2O @ 75-50-100 kg ha-1 and that of protein content up to N-P2O5-K2O @ 75-50-75 kg ha-1. The sugar content, vitamin C and Ã¢- carotene contents were found progressively declined with added irrigation and fertility levels. Thus, irrigation at IW/CPE 0.8 with application of N-P2O5-K2O @ 75-50-75 kg ha-1 resulted in greater gross return, net return and B: C ratio.